2019 11th International Congress on Ultra Modern Telecommunications and Control Systems and Workshops (ICUMT) 2019
DOI: 10.1109/icumt48472.2019.8970942
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Intelligent Intrusion Detection Systems for VANETs

Abstract: Vehicular Ad hoc Networks (VANETs) are a growing area that continues to gain interest with an increasing diversity of applications available. These are the underlying network for Intelligent Transportation Systems (ITS), a set of applications and services that aim to provide greater security and comfort to drivers and passengers.However, the characteristics and size of a VANET make it a security challenge. It has been a subject of study, with several research works aimed at this problem, usually involving cryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Based on their survey it is observed that no specific information is provided regarding datasets and its operations which are performed on it like training, validating of data and detection of attacks and beacon messages in communication. The authors in [8] Mohammad Asif Hossain and Wahidah Md Shah proposed they have considers the award and penalty scheme which is based on the case of student and teacher learning process. With this scheme it can reduce the network overhead and delay.…”
Section: Related Workmentioning
confidence: 99%
“…Based on their survey it is observed that no specific information is provided regarding datasets and its operations which are performed on it like training, validating of data and detection of attacks and beacon messages in communication. The authors in [8] Mohammad Asif Hossain and Wahidah Md Shah proposed they have considers the award and penalty scheme which is based on the case of student and teacher learning process. With this scheme it can reduce the network overhead and delay.…”
Section: Related Workmentioning
confidence: 99%
“…VANET security is a well-researched topic, with solutions ranging from the most common and traditional Public Key Infrastructure (PKI) [10][11][12][13][14] to others, such as IDbased or situation-modeling approaches [15]. However, the approach using IDSs, more precisely, intelligent IDSs, is more recent, with interest growing since 2010 [8]. In the Systematic Literature Review (SLR) performed in previous works [8], it was found that the most common approach type of solution used a hierarchical architecture, with 10 of the 19 research works choosing this approach.…”
Section: Related Workmentioning
confidence: 99%
“…However, the approach using IDSs, more precisely, intelligent IDSs, is more recent, with interest growing since 2010 [8]. In the Systematic Literature Review (SLR) performed in previous works [8], it was found that the most common approach type of solution used a hierarchical architecture, with 10 of the 19 research works choosing this approach.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations